FRI0435 Interleukin-35 is Overexpressed in Systemic Sclerosis and its Serum Levels are Elevated in Early Disease. (9th June 2015) - Tomcik, M.; Zerr, P.; Palumbo-Zerr, K.; Storkanova, H.; Hulejova, H.; Spiritovic, M.; Kodet, O.; Stork, J.; Becvar, R.; Vencovsky, J.; Pavelka, K.; Filkova, M.; et al.
Abstract : Background: Interleukin-35 (IL-35) is the most recent addition to the IL-12 family, which also includes IL-12, IL-23 and IL-27. IL-35 consists of p35/IL-12a and EBI3/IL-27b chains and exerts immunomodulatory activities in experimental and human autoimmune inflammatory conditions. Its potential role has been proposed in the pathogenesis of rheumatoid arthritis, sarcoidosis and systemic lupus erythematosus. However, its role in systemic sclerosis (SSc) has not been studied to date. Objectives: To assess IL-35 expression in skin, dermal fibroblasts and circulation of SSc patients and characterize its potential association with SSc-related features. Methods: Expression of IL-35 in skin and dermal fibroblasts was quantified by qPCR, immunohistochemistry and immunofluorescence. Serum levels of IL-35 (by high sensitivity ELISA, USCN Life Sciences Inc., Hubei, PRC), CRP (by turbidimetry), ANA (by immunofluorescence) and autoantibodies of the ENA complex (by immunoblot) were measured in 40 SSc patients who met the EULAR/ACR 2013 criteria for SSc. Serum IL-35 was determined in 40 age- and sex-matched healthy controls. Results: IL-35 chains EBI3 and p35 were overexpressed in the fibrotic skin of patients with SSc compared to that of healthy controls on both mRNA (p<0.05, p<0.05) and protein level (p<0.001, p<0.001). In fibrotic SSc skin, prominent staining for both IL-35 subunits was detected in dermal fibroblasts, myofibroblasts and perivascular inflammatory cells. Overexpression of IL-35 persisted in cultured dermal fibroblasts from SSc patients which maintained increased mRNA (p<0.05, p<0.05) and protein level of both IL-35 subunits and released increased levels of IL-35 into supernatants (p<0.05) compared to healthy fibroblasts. Stimulation with TGF-β increased the mRNA (p<0.05, p<0.05) and protein levels of both IL-35 chains, and enhanced the release of IL-35 into the supernatants (p<0.05), as well. Incubation with recombinant IL-35 induced an activated phenotype in resting fibroblasts and enhanced the release of collagen. IL-35 serum levels were increased in patients with SSc compared to healthy controls (mean ± SEM: 61.3±20.2 vs. 8.2±0.8 pg/ml, p<0.0001). Serum IL-35 negatively correlated with disease duration (p<0.05, r=-0.352), and was increased in patients with early SSc pattern on capillaroscopy assessment compared to those with active and late SSc patterns (p<0.05, p<0.05). No correlations of serum IL-35 with other SSc-related features were observed. Conclusions: The present study demonstrates an overexpression of IL-35 in SSc skin, dermal fibroblasts and serum. TGF-β induces IL-35, which in turn activates resting fibroblasts and enhances the release of collagen thereby contributing to aberrant TGF-β signaling in SSc. Elevated serum IL-35 is associated with early, inflammatory stages of SSc. Acknowledgements: Supported by IGA12440-4, MHCR023728. Disclosure of Interest: None declared